Identification of mammalian-adapting mutations in the polymerase complex of an avian H5N1 influenza virus - Taft, Andrew S.; Ozawa, Makoto; Fitch, Adam; Depasse, Jay V.; Halfmann, Peter J.; Hill-Batorski, Lindsay; Hatta, Masato; Friedrich, Thomas C.; Lopes, Tiago J. S.; Maher, Eileen A.; Ghedin, Elodie; Macken, Catherine A.; et al. (Nature communications, 2015)
Avian influenza viruses of the H5N1 subtype pose a serious global health threat due to the high mortality (>60%) associated with the disease caused by these viruses and the lack of protective antibodies to these viruses in the general population. The factors that enable avian H5N1 influenza viruses to replicate in humans are not completely understood. Here we use a high-throughput screening approach to identify novel mutations in the polymerase genes of an avian H5N1 virus that confer efficient polymerase activity in mammalian cells. Several of the identified mutations (which have previously been found in natural isolates) increase viral replication in mammalian cells and virulence in infected mice compared with the wild-type virus. The identification of amino-acid mutations in avian H5N1 influenza virus polymerase complexes that confer increased replication and virulence in mammals is important for the identification of circulating H5N1 viruses with an increased potential to infect humans. Understanding the factors that enable some bird flu viruses to infect humans is important for the identification of circulating viruses with higher potential to infect us. Here, Taft et al. identify novel mutations in the polymerase of an avian H5N1 virus that help the virus to replicate in human cells and in mice